2008
DOI: 10.1182/blood-2008-03-147322
|View full text |Cite
|
Sign up to set email alerts
|

STAT-3 and ERK 1/2 phosphorylation are critical for T-cell alloactivation and graft-versus-host disease

Abstract: Graft-versus-host disease (GVHD) is a serious complication of allogeneic bone marrow transplantation, and donor T cells are indispensable for GVHD. Current therapies have limited efficacy, selectivity, and high toxicities. We used a novel flow cytometry technique for the analysis of intracellular phosphorylation events in single cells in murine BMT models to identify and validate novel GVHD drug targets. [1][2][3][4][5][6][7] This method circumvents the requirement for large numbers of purified cells, unlike w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 25 publications
4
50
0
1
Order By: Relevance
“…[32][33][34]71 Downregulation of IL-18R in ST2-deficient T cells may be due to an impaired MAPK-dependent pathway, 15,17,32 since the regulation of the receptor has been shown to be MAPK-dependent. 22,36,37 Also, the activation of stress-activated protein kinases such as MAPK 72 and ERK 73 were previously shown to be relevant for the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34]71 Downregulation of IL-18R in ST2-deficient T cells may be due to an impaired MAPK-dependent pathway, 15,17,32 since the regulation of the receptor has been shown to be MAPK-dependent. 22,36,37 Also, the activation of stress-activated protein kinases such as MAPK 72 and ERK 73 were previously shown to be relevant for the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…16 Single-cell analysis of ERK1/2 phosphorylation in murine T cells suggested that ex vivo MEK inhibition inhibited alloreactivity, suggesting the potential to ameliorate GVHD. 17 MEK1/2 inhibitors are being tested for efficacy in multiple cancers dependent on RAS/MEK/ERK signaling, with little apparent hematologic toxicity reported in over 60 ongoing human clinical trials. 18,19 Recently, extremely promising results have been evident in multiple cancer trials, either using MEK inhibition alone or with other targeted inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…47 That study showed the presence of phosphorylated STAT3 in dividing cells after BMT. 48 Furthermore, the preincubation of donor T cells with a small molecule inhibitor of STAT3 could reduce donor CD8 T-cell expansion and …”
Section: Socs3 Regulates Gvhd 293mentioning
confidence: 99%